Engineer Ari and the Passover rush - Cohen, Deborah Bodin, 1968- (Kar-Ben Publishing, 2015)
"In 1893, Engineer Ari is in a rush to get his train to Jerusalem and back before Passover, and he still needs many things for his seder plate. Luckily he has many friends to help"--